2018
DOI: 10.1111/jace.16050
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural comparison of the AH3 phase in the hydration of three structural modifications of ye'elimite

Abstract: This paper investigated the hydration and formation of the AH3 phase in three structural modifications of ye'elimite (namely, ss‐ye'elimite, Sr‐ye'elimite, and Ba‐ye'elimite). Three structural modifications of ye'elimite were synthesized, and their reactions with water were studied. The similarities and differences of the microstructure of the final AH3 phase formed during the hydration of different structural modifications of ye'elimite were investigated using a multitechnique approach. The crystal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(50 reference statements)
3
9
0
Order By: Relevance
“…Recent work has reported that Ba-ye'elimite had the fastest hydration rate among the three ye'elimite in the deionized water environment. 18 This work further confirmed this result in various alkaline environments. The quantitative phase analysis for each hydrated paste was carried out using Rietveld refinement with the internal method.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Recent work has reported that Ba-ye'elimite had the fastest hydration rate among the three ye'elimite in the deionized water environment. 18 This work further confirmed this result in various alkaline environments. The quantitative phase analysis for each hydrated paste was carried out using Rietveld refinement with the internal method.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…15 Additionally, a recent work, exploring the structure of the AH 3 phase formed by the three ye'elimite hydrated with H 2 O, suggested that the AH 3 formed by ss-ye'elimite and Srye'elimite had a larger crystal size; however, AH 3 formed by Ba-ye'elimite presented a smaller crystal size according to the saturation index. 18 It is worth noting that the AH 3 might be initially formed with an amorphous nature. Le Saout et al, 17 for instance, studying the AH 3 in CAC cements using a low L/ S ratio, found that no signals of the AH 3 phase can be detected in XRD or TG measurements at the early age (before several hours), which indicated that the amorphous AH 3 may be present in this stage.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations